Portrait of a spy - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2011)
After failing to stop a suicide bomber attack in London, master art restorer and assassin Gabriel Allon is summoned by the CIA and is faced with an organization riddled with dissent--and ill-equipped to deal with the deadly new face of global jihadist terror.